SOSIALISASI DIGITALISASI MARKETING DAN PENCATATAN AKUNTANSI PADA UMKM DI DESA SELEBUNG - Syarifah Massuki Fitri; Muhammad Syukri; Suandi Suandi (Devote: Jurnal Pengabdian Masyarakat Global, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in supporting the community's economy. However, MSMEs still face various challenges in managing their businesses, particularly in digital marketing and accounting. This community service activity aims to improve the knowledge and skills of MSMEs in Selebung Village in utilizing digital marketing and implementing simple accounting records in business management. The activity was implemented through several stages: observation and problem identification, program planning, outreach and training, and mentoring for 15 participants. The methods used included lectures, discussions, and simple practices related to the use of digital media for marketing activities and recording cash inflows and outflows. The results of the activity showed that most MSMEs previously maintained manual financial records and had not optimally utilized social media to promote their products. After participating in the outreach and training activities, participants experienced an increased understanding of the importance of accounting records and the use of digital platforms as a means of product marketing. Through this activity, it is hoped that MSMEs will be able to manage their businesses more effectively, increase their competitiveness, and support business sustainability in the digital era.